Protocolo para screening de habilidades musicais (PSHM) - Koga, Fabiana Oliveira (Editora Oficina Universitária, 2021)
This book, the result of Fabiana O. Koga's intense research work, makes an original and unique contribution to the study of high abilities/giftedness, by highlighting musical talent, which is undervalued in the current educational scenario, considering that education music does not find space in most school curricula. By going through the chapters of this work, it is possible to understand the history of music teaching, the concept of talent and musical talent, as well as the scenario of national and international research on this topic. The author also highlights the important role of the school in identifying students with musical talent, so that enrichment is offered or referral to projects and institutions that encourage the full development of these potentials. In this way, conditions can be provided for them to follow the path of professionalization and the construction of an identity. Thus, the construction of the Musical Skills Screening Protocol (PSHM), in printed and virtual modalities, will contribute greatly, as it will give visibility to those students who demonstrate musical talent, giving urgency to the reflection on public policies for music education and special education and allowing these individuals the opportunity to take the first steps towards their self-realization.